Therapeutic plasma exchange in neuroimmunologic disease: 60 patients experience (Annals of Medical Research, 2021)
Aim: We aimed to determine the results, safety, and applicability of therapeutic plasma exchange (TPE) in neurological diseases.Materials and Methods: We performed a retrospective analysis in between 2014-2019. In the evaluation of response to treatment (RT), patients were divided into 4 groups: full recovery (RT1), partial recovery (RT2), stationary or worse (RT3), exitus (RT4). TPE treatment was evaluated effective in patients with RT1 and RT2. Patients' data were compared between group 1 (TPE as first line treatment) and group 2 (TPE as additional therapy).Results: TPE procedure was applied to 199 patients, 1330 times. Sixty neurological patients (mean age 51.5±17.05; 24 female) underwent 356 TPE procedures on average 6.2 sessions. After TPE, functional status was RT1:3, RT2:19, RT3:28, RT:10. TPE was an effective treatment in 36.6% of patients. Disease distribution Guillain Barre syndrome (n:26), myasthenia gravis (n:8), autoimmune encephalitis (n:6), neuromyelitis optica (n:5), transverse myelitis (n:5), vasculitis (n:3), chronic demyelinating inflammatory polyneuropathy (n:2), multiple sclerosis (n:2), Morvan syndrome (n:1), myeloradiculitis (n:1) and polymyositis (n:1). 7 patients (11.6%) were included in group 1 and 53 patientswere in group 2. TPE was started after 9.7 days (±6.9) due to insufficient response. Complications were found in 6 patients (10%).  The duration of hospitalization was 28.1 (±13.1) in group 1 and 32.9 (±19) days in group 2 (p: 0.01).Conclusion: Our experience has supported that TPE is a safe and effective treatment option for a wide range of antibody-related neurological disorders, especially if it is the first treatment option.